Rhenium Tricarbonyl Complexes of Azodicarboxylate Ligands - Jordan, Rose; Niazi, Maryam; Schäfer, Sascha; Kaim, Wolfgang; Klein, Axel (Molecules (Basel, Switzerland), 2022)
The excellent π-accepting azodicarboxylic esters adcOR (R = Et, iPr, tBu, Bn (CH2-C6H5) and Ph) and the piperidinyl amide derivative adcpip were used as bridging chelate ligands in dinuclear Re(CO)3 complexes [{Re(CO)3Cl}2(µ-adcOR)] and [{Re(CO)3Cl}2(µ-adcpip)]. From the adcpip ligand the mononuclear derivatives [Re(CO)3Cl(adcpip)] and [Re(CO)3(PPh3)(µ-adcpip)]Cl were also obtained. Optimised geometries from density functional theory (DFT) calculations show syn and anti isomers for the dinuclear fac-Re(CO)3 complexes at slightly different energies but they were not distinguishable from experimental IR or UV–Vis absorption spectroscopy. The electrochemistry of the adc complexes showed reduction potentials slightly below 0.0 V vs. the ferrocene/ferrocenium couple. Attempts to generate the radicals [{Re(CO)3Cl}2(µ-adcOR)]•− failed as they are inherently unstable, losing very probably first the Cl− coligand and then rapidly cleaving one [Re(CO)3] fragment. Consequently, we found signals in EPR very probably due to mononuclear radical complexes [Re(CO)3(solv)(adc)]•. The underlying Cl−→solvent exchange was modelled for the mononuclear [Re(CO)3Cl(adcpip)] using DFT calculations and showed a markedly enhanced Re-Cl labilisation for the reduced compared with the neutral complex. Both the easy reduction with potentials ranging roughly from −0.2 to −0.1 V for the adc ligands and the low-energy NIR absorptions in the 700 to 850 nm range place the adc ligands with their lowest-lying π* orbital being localised on the azo function, amongst comparable bridging chelate N^N coordinating ligands with low-lying π* orbitals of central azo, tetrazine or pyrazine functions. Comparative (TD)DFT-calculations on the Re(CO)3Cl complexes of the adcpip ligand using the quite established basis set and functionals M06-2X/def2TZVP/LANL2DZ/CPCM(THF) and the more advanced TPSSh/def2-TZVP(+def2-ECP for Re)/CPCMC(THF) for single-point calculations with BP86/def2-TZVP(+def2-ECP for Re)/CPCMC(THF) optimised geometries showed a markedly better agreement of the latter with the experimental XRD, IR and UV–Vis absorption data.